Mechanisms of control and resistance in the devolved work of public school principals in New South Wales. (2nd January 2023) - Dabaja, Isabella
ABSTRACT: Globally, New Public Management reforms have transformed work in many areas of the public sector. A key aspect of these reforms has been devolution: the provision of greater local autonomy over resources and decision making as part of a broader decentralisation strategy. Important questions about managers' work in devolved settings, not in the least in public education, remain to be addressed. The 2012–18 'Local Schools, Local Decisions' reform to public education in the Australian state of New South Wales was framed by familiar aims: to achieve 'efficiency and effectiveness' through greater local control. Recognising principals as the nexus of this ostensible local authority, principals' work in the final stages of the reform's implementation were investigated. Through the utilisation of labour process theory to examine tensions in this focal employment relationship, three key control mechanisms in the work of principals were identified: a reduction of the indeterminacy gap through principals' management of resources; the degradation of work under devolution; and the legitimation of the state through principals' work.